(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Electronic commerce is an electronic commerce. Open door systems such as B2B, B2C, C2C and the like help the buyer and buyer markets by creating an electronic basis for future challenges. Web-based companies have reformed their businesses and changed their competition with the web. The PC- based communications system creates a web-based shopping center for buyers and businesses. For example, along with improvements in the Internet and web-based innovations, developments between the traditional markets and the global electronic shopping center are beginning to limit, among other things, the size of the company’s capital. India is showing a great improvement in electronic commerce. The minimum effort of the PC and the increasing use of the Internet is one of the objectives of this project. The commercial network in India is increasingly aware of the open doors that online businesses offer. The main objective of this article is to examine the role of electronic commerce in current commerce.